Motor Deficits Are Produced By Removing Some Cortical Transplants Grafted Into Injured Sensorimotor Cortex of Neonatal Rats. (1991) - Sandor, Rick; Gonzalez, Manuel F.; Moseley, Michael; Sharp, Frank R.
Abstract : Fetal frontal cortex was transplanted into cavities formed in the right, motor cortex of neonatal rats. As adults, the animals were trained to press two levers in rapid succession with their left forelimb to receive food rewards. Once they had reached an optimal level of performance, the effect of removing their transplants was assessed. Surgical removal of transplants significantly impaired the performance of 2 of 4 subjects. Placing a crossstrain skin graft to induce the immunological rejection of the transplants produced a behavioral deficit in 1 of 2 subjects with complete transplant removal. Skin grafts produced no behavioral effects in four subjects that had surviving transplants. Since the motor deficit produced by transplant removal resembled those observed following the removal of normal motor cortex, we propose that these three transplants functioned within the host brain. Histology Showed that the procedures used to remove cortical grafts did not injure any host brains. Therefore, host brain damage is unlikely to account for the behavioral deterioration that followed transplant removals.